New Advances in Oil, Gas and Geothermal Reservoirs (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The demand for global fossil energy continues to be strong, meaning that the exploitation of oil and gas resources is still very important. In addition, due to the continuous reduction in conventional oil and gas recoverable resources, the development of unconventional oil and gas resources and geothermal energy has gradually become an important replacement. Therefore, it is urgent to improve the existing mechanism analysis, research methods and engineering technology to improve the production and development efficiency of oil, gas, and geothermal resources. This reprint presents 11 recent works on the application of new theories and technologies in oil, gas, and geothermal reservoirs. The content covers well-drilling, cementing, hydraulic fracturing, improved oil recovery, conformance control, and geothermal energy development. The new progress presented in this reprint will help scientists and researchers to better understand and master the latest theories and techniques for oil, gas, and geothermal reservoirs, which has important practical significance for the economical and effective development of oil, gas, and geothermal resources.